Diversity and Ecology of Invasive Plants - Charan Sahu, Sudam; Kumar, Sanjeet (IntechOpen, 2019)
This book, Diversity and Ecology of Invasive Plants, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of invasive species biology. The book comprises chapters authored by various researchers and edited by experts active in the field of conservation of biodiversity. All chapters are complete in itself but united under a common topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on diversity, distribution, and ecological consequences of invasive species and opens new possible research paths for further developments.